Tathbiq Thariqah Al-Tikrar Fi Tahsin Al-Adaâ€™ Al-Shauti li Al-Athfal fi Raudhah Al-Qurâ€™an â€œNur Al-Haqâ€ Labung - Safreni, Junia (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This research aims to answer the question is whether the method of repetition in improving the vocal performance of the children of the Qur'an Kindergarten "Noor al-Haq" in the village of Labung Candung is effective. The method used is descriptive quantitative research method. It is using statistical formulas based on research problems. At the same time, to find out the effectiveness of the repetition method in improving the vocal performance of the children of the Qurâ€™an Kindergarten "Noor al-Haq" in the village of Labung Candung, the researcher uses the t-test formula at levels of 1% and 5%, meaning 22 df, level of 1%: 2.76377 and 5% level of 1.81246. Therefore, the level of significance of the calculation t compared to the table t, the null hypothesis is rejected and the alternative chance is accepted, and therefore the conclusion is that there is an effectiveness of the repetition method in improving the vocal performance of the children of Al-Quran Kindergarten "Noor Al-Haq" in the village of Labung Candung. ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø© Ø¹Ù† Ø§Ù„Ø³Ø¤Ø§Ù„ Ù‡Ùˆ Ù‡Ù„ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙƒØ±Ø§Ø± ÙÙŠ ØªØØ³ÙŠÙ† Ø§Ù„Ø£Ø¯Ø§Ø¡ Ø§Ù„ØµÙˆØªÙŠ Ù„Ø£Ø·ÙØ§Ù„ Ø±ÙˆØ¶Ø© Ø§Ù„Ù‚Ø±Ø¢Ù† "Ù†ÙˆØ± Ø§Ù„ØÙ‚" ÙÙŠ Ù‚Ø±ÙŠØ© Ù„Ø§Ø¨ÙˆÙ†Ø¬ Ø¬Ø§Ù†Ø¯ÙˆÙ†Ø¬ ÙØ¹Ù‘Ø§Ù„Ø©. Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù‡ÙŠ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙ…ÙŠ Ø§Ù„ÙˆØµÙÙŠ. ÙˆÙ‡ÙŠ Ø¨Ø§Ø³ØªØØ¯Ø§Ù… Ø§Ù„ØµÙŠØº Ø§Ù„Ø¥ØØµØ§Ø¦ÙŠØ© Ø¹Ù„Ù‰ Ø£Ø³Ø§Ø³ Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ø¨ØØ«. ÙˆÙÙŠ Ø§Ù„ÙˆÙ‚Øª Ù†ÙØ³Ù‡ØŒ Ù„Ù…Ø¹Ø±ÙØ© ÙØ¹Ù‘Ø§Ù„ÙŠØ© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙƒØ±Ø§Ø± ÙÙŠ ØªØØ³ÙŠÙ† Ø§Ù„Ø£Ø¯Ø§Ø¡ Ø§Ù„ØµÙˆØªÙŠ Ù„Ø£Ø·ÙØ§Ù„ Ø±ÙˆØ¶Ø© Ø§Ù„Ù‚Ø±Ø¢Ù† "Ù†ÙˆØ± Ø§Ù„ØÙ‚" ÙÙŠ Ù‚Ø±ÙŠØ© Ù„Ø§Ø¨ÙˆÙ†Ø¬ Ø¬Ø§Ù†Ø¯ÙˆÙ†Ø¬ØŒ ØªØ³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ«Ø© ØµÙŠØºØ© Ø§Ø®ØªØ¨Ø§Ø± t Ø¹Ù†Ø¯ Ù…Ø³ØªÙˆÙŠØ§Øª 1% Ùˆ 5%ØŒ ÙŠØ¹Ù†ÙŠ 22 dfÂ Â  Ù…Ø³ØªÙˆÙ‰ 1% : 2.76377Ùˆ Ù…Ø³ØªÙˆÙ‰ 5% 1.81246. ÙˆÙ„Ø°Ù„Ùƒ Ù…Ø³ØªÙˆÙ‰ Ø¯Ù„Ø§Ù„Ø© Ø§Ù„ØØ³Ø§Ø¨ t Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨Ø§Ù„Ø¬Ø¯ÙˆÙ„ tØŒ ÙŠØªÙ… Ø±ÙØ¶ Ø§Ù„ÙØ±Ø¶ÙŠØ© Ø§Ù„ØµÙØ±ÙŠØ© ÙˆÙŠØªÙ… Ù‚Ø¨ÙˆÙ„ Ø§Ù„ÙØ±ØµÙŠØ© Ø§Ù„Ø¨Ø¯ÙŠÙ„Ø©ØŒ ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ ÙØ¥Ù† Ø§Ù„Ø§Ø³ØªÙ†ØªØ§Ø¬ Ù‡Ùˆ Ø£Ù† Ù‡Ù†Ø§Ùƒ ÙØ¹Ù‘Ø§Ù„ÙŠØ© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙƒØ±Ø§Ø± ÙÙŠ ØªØØ³ÙŠÙ† Ø§Ù„Ø£Ø¯Ø§Ø¡ Ø§Ù„ØµÙˆØªÙŠ Ù„Ø£Ø·ÙØ§Ù„ Ø±ÙˆØ¶Ø© Ø§Ù„Ù‚Ø±Ø¢Ù† "Ù†ÙˆØ± Ø§Ù„ØÙ‚" ÙÙŠ Ù‚Ø±ÙŠØ© Ù„Ø§Ø¨ÙˆÙ†Ø¬ Ø¬Ø§Ù†Ø¯ÙˆÙ†Ø¬.